The regulatory environment and its effect on casino operations in the Czech Republic. - Bezrodnova, Alisa (2025)
This bachelor thesis is focused the analysis of the gambling regulation system in the Czech Republic. The center of attention - its impact on casino operations. The aim of my research is to identify how national legislation, as well as tax and licensing regulations, shape the structure and behavior of the gambling market in the Czech Republic. The thesis contains a legal analysis, interpretation of economic data and a comparative overview with neighboring countries in Central Europe. It also presents a SWOT analysis of the Czech gambling industry and discusses the opportunities and challenges faced by Czech and foreign operators under the current regulatory framework. The results show that strict measures place a significant burden on operators and reduce investment attractiveness, while contributing to player protection and market transparency.